Application of gamification in history learning: Its impact on students' motivation and understanding of historical concepts - Suprianto, Suprianto; Yuliantri, Rhoma Dwi (Universitas Negeri Malang, 2025)
History learning is often considered boring and challenging for students to understand because conventional methods are passive, so innovative strategies such as gamification are needed to increase motivation and understand historical concepts more effectively and meaningfully. This research uses a quasi-experimental design with a pretest-posttest control group design. The sample consisted of two classes of XI SMA (32 students per class). Data collection instruments use multiple-choice tests to test understanding of historical concepts and questionnaires to measure students' learning motivation. Data analysis includes normality, homogeneity, t-test, and N-Gain Score tests to measure the effectiveness of gamification. The research results show that gamification increases historical understanding more significantly (N-Gain = 0.605, medium-high category) than conventional methods (N-Gain = 0.274, low category). In addition, student motivation in the experimental class increased from 6.25% to 62.50% for the high category, while in the control class it only increased from 6.25% to 12.50%. So it is concluded that gamification has proven to be more effective than conventional methods in increasing students' involvement, motivation, and understanding of historical concepts.